Computational Fluid Dynamics Simulation of Cooling System for Copper Smelter Gases by Teniente Converter with Evaporative Cooler [Modelación y Simulación Fluido-Dinámica Computacional de Sistema de Enfriamiento de Gases Para Fundición de Cobre Mediante Convertidor Teniente Con Enfriador Evaporativo] - Hurtado-Cruz, J; Vargas-Norambuena, J; Perez-Cortes, S (Elsevier B.V., 2017)
In the copper sulfides smelting process, the Teniente-type converter generates highly corrosive and toxic gases, which is why treating them is crucial in order to avoid environmental damage. The present study proposes a new methodology to simulate the capture and cooling system of smelting gases through the application of Computational Fluid Dynamics (CFD) to the gases that emanate from a Teniente-type converter, where a series of assumptions that allow the adaptation of the physical model for the CFD simulation are proposed along with the validation of the results using real industrial-scale instruments. By applying this method, it is possible to obtain a behavioral simulation model of the smelting gases with an acceptable relative error. In practical terms, this means that the tendencies that metallurgical gases show in the simulation flowing through the bell and the cooling chamber can be trusted to predict the thermal behavior of the gases contained in the gas management network. © 2016 CIMNE (Universitat Politècnica de Catalunya)